PERSIAPAN IMPLEMENTASI TANDA TANGAN DIGITAL UNTUK AUTENTIKASI DOKUMEN REKAM MEDIS ELEKTRONIK DI RSUD dr. H. MOCH ANSARI SALEH BANJARMASIN - Muhammad Rashif Anshari; Himalia Putri; Galih Persadha (Politeknik Unggulan Kalimantan, 2023)
The use of digital signatures in electronic medical records serves as a tool for authentication and verification of the identity of the signatory as well as the integrity and authenticity of electronic information. The purpose of this study was to determine the readiness of implementing digital signatures at dr. H. Moch Ansari Saleh Banjarmasin based on 5M aspects and legal aspects. This study used a descriptive qualitative method with data collection techniques using interviews with 4 informants, namely the head of the medical record unit, public relations, PPA doctors and IT. The research results for human aspects are known to be suitable for human resources from the structure and background. Money, the hospital is ready in terms of budget. Material, the availability of support for electronic signature activities. Method, there is no SOP regarding electronic signatures on RME. Machine, facilities and infrastructure are sufficient to support. Legal, there is still no clear regulation regarding the application of electronic signatures in RME. Based on the results of the study it can be concluded that the readiness of dr. H. Moch. Ansari Saleh Banjarmasin in terms of 5M and legal aspects, namely not ready in terms of fingerprint facilities for patients, SOP and Legal aspects for applying digital signatures to electronic medical record documents.